(untitled) (American Journal of Technology and Applied Sciences, 2025)
The article also discusses modern methods of crop yield assessment and forecasting, including the use of regression analysis based on satellite data. Particular attention is paid to short-term and medium-term forecasts that meet the requirements of simplicity, cost-effectiveness and automation. The proposed approaches allow one to take into account the depth of the forecast, which determines the choice of intuitive or formalized methods. The work contributes to the development of tools for sustainable agriculture and the maintenance of soil ecosystem services.